2018
DOI: 10.1097/scs.0000000000004542
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Cell Viability Immediately After Osteotomy for Implants With Drills and Piezosurgery: Immunohistochemistry Analysis

Abstract: This study will provide data so that the authors can recycle the drills and tips for implant placement, thus enabling a better cell viability for osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recent literature suggests that the ultrasonic vibration produced by piezosurgery stimulates early osteocyte apoptosis, which results in bone remodeling (Zou et al, 2019 ). Other studies found more interleukin‐1β, an actor in osteoclast differentiation in piezoelectric surgery sites than in bur surgery sites (Chenu et al, 1994 ; Lee et al, 2006 ; Preti et al, 2007 ). Piezosurgery also appears to be less damaging to the vitality of osteoprogenitor cells such as osteoblasts (Pereira et al, 2018 ) and osteocytes (Anesi et al, 2018 ) when compared with rotary instruments.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent literature suggests that the ultrasonic vibration produced by piezosurgery stimulates early osteocyte apoptosis, which results in bone remodeling (Zou et al, 2019 ). Other studies found more interleukin‐1β, an actor in osteoclast differentiation in piezoelectric surgery sites than in bur surgery sites (Chenu et al, 1994 ; Lee et al, 2006 ; Preti et al, 2007 ). Piezosurgery also appears to be less damaging to the vitality of osteoprogenitor cells such as osteoblasts (Pereira et al, 2018 ) and osteocytes (Anesi et al, 2018 ) when compared with rotary instruments.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies found more interleukin-1β, an actor in osteoclast differentiation in piezoelectric surgery sites than in bur surgery sites (Chenu et al, 1994;Lee et al, 2006;Preti et al, 2007). Piezosurgery also appears to be less damaging to the vitality of osteoprogenitor cells such as osteoblasts (Pereira et al, 2018) and osteocytes (Anesi et al, 2018) when compared with rotary instruments. In addition, it has been shown that blood supply around a surgical bone defect was better preserved with piezosurgery (Reside et al, 2015).…”
Section: Automated Segmentationmentioning
confidence: 92%
“…In support of this, in a recent study [2,10], the authors showed that osteotomies of the adult rabbit cranial vault with piezoelectric devices heal faster than those with traditional rotating osteotomes, and in the bone samples cut with PM and PP devices, the number of osteoclasts is higher with respect to the traditional rotating one, suggesting greater bone remodeling activity. In addition, by immunohistochemistry analysis, Pereira and collaborators [49] showed that the bone formation and resorption responses were greater with piezosurgery than with conventional drilling, suggesting that the implant preparation with piezoelectric surgery favors cell viability, thereby improving bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the in vivo stimulation by UOD cut might lead mesenchymal cells to activate proliferative and osteogenic differentiation and then regenerate faster than ROD cut tissue. Chiriac et al [17] showed that UOD cutting could maintain osteocyte health in the bone cutting zone and that the outgrown cells had osteoblastic characteristics; additionally, other researchers indicated that osteoblastic cells harvested with a UOD had high cell viability [18,19] . We suggest that the rapid regeneration in UOD-cut tissue compared to ROD-tissue tissue occurred because ultrasound stimulation does not damage osteoblastic cells but rather preserves or even activates then.…”
Section: Discussionmentioning
confidence: 99%